Modeling and monitoring methods for industrial robots based on digital twin - XU Jian; ZHAO Yijian; LIU Gaofeng; ZHENG Zili; YAN Huanying (Xi'an Gongcheng Daxue xuebao)
In view of the issues such as opaque data and monitoring blind spots in industrial robots, study was conducted on physical industrial robots, leading to the development of a digital twin robot monitoring system. Firstly, modeling of virtual robots was accomplished from three dimensions: geometric, physical, and logical. Secondly, based on the open platform communications united architecture (OPC UA), data collection and communication for robots were implemented. User display interfaces were designed to achieve real-time visualization of data. Finally, through robot simulation experiments, the relative position errors of the robot end effector in the X, Y, and Z coordinates were determined to be 0.48%, 0.32%, and 0.27%, respectively. The maximum error in joint angles of the robot, verified through synchronized experiments using a digital twin robot monitoring system, was found to be 0.31°. The experimental results demonstrate that the method can achieve motion data monitoring for digital twin industrial robots, reducing the risk of accidents and failures in the production process. It provides insights and directions for the development of intelligent industrial robots.